Penegakkan Hukum Terhadap Kejahatan Dunia Maya - Sanjaya, Aditya Wiguna; Kristanto, Kiki (WELFARE STATE Jurnal Hukum, 2025)
This study aims to examine the government’s efforts in enforcing the law against cybercrime, while also analyzing the supporting and inhibiting factors that influence its implementation. The research method employed is normative legal research with both legislative and conceptual approaches, emphasizing the analysis of applicable legal norms and relevant theoretical frameworks. The findings indicate that the government, through law enforcement institutions such as the Indonesian National Police (Polri) and Civil Servant Investigators (PPNS) under the Ministry of Communication and Informatics (Kemenkominfo), plays a crucial role in enforcing laws against cybercrime based on the Information and Electronic Transactions Law (ITE Law). The primary supporting factor lies in the availability of adequate legal substance. However, challenges remain, including the limited number of trained personnel and the low level of public understanding regarding information technology. Therefore, effective law enforcement against cybercrime requires greater attention to enhancing the capacity of law enforcement resources, strengthening institutional support, and improving public digital literacy and awareness of information security.